2021
DOI: 10.1021/acs.jafc.0c06952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Biotechnologically Produced Oyster Mushroom (Pleurotus sajor-caju) on the Gut Microbiota and Microbial Metabolites in Obese Zucker Rats

Abstract: Mushrooms are a rich source of dietary fiber. This study aimed to characterize the modulation of colonic microbiota in Zucker rats after supplementing their diet with a biotechnologically produced oyster mushroom (Pleurotus sajor-caju). Microbiota composition and short chain fatty acids (SCFAs) in the colon and bile acids in the plasma of the rats were analyzed to assess the effects of P. sajor-caju supplementation on the microbiota in the colon and its interplay with the host in the event of hepatic steatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Mushrooms were widely reported regulating gut microbiota via improving the levels of probiotics and reducing the growth of pathogens. A recent study reported that dietary fibers from oyster mushroom (P. sajor-caju) could increase the abundance of smallchain fatty acids (SCFAs) producing bacterial genera and inhibit the growth of intestinal pathogens (Maheshwari et al, 2021). Simultaneously, fibers impact on the bioavailability of functional constituents in the colon and are benefit for human health.…”
Section: Potential Bioactivitymentioning
confidence: 99%
“…Mushrooms were widely reported regulating gut microbiota via improving the levels of probiotics and reducing the growth of pathogens. A recent study reported that dietary fibers from oyster mushroom (P. sajor-caju) could increase the abundance of smallchain fatty acids (SCFAs) producing bacterial genera and inhibit the growth of intestinal pathogens (Maheshwari et al, 2021). Simultaneously, fibers impact on the bioavailability of functional constituents in the colon and are benefit for human health.…”
Section: Potential Bioactivitymentioning
confidence: 99%
“…A polysaccharide from Tremella fuciformis hindered the differentiation of 3T3-L1 adipocytes by reducing the mRNA expression, suggesting that this polysaccharide could be a potential prebiotic for obesity [74]. Cure of adipocytes with G. lucidum diminished adipogenic record factor articulation, which increases glucose and lipid transport and activates AMPK pathway, suggesting its potential as an anti-obesity drug [113].…”
Section: Effect Of Mushroom Consumption On Gut Microbiotamentioning
confidence: 99%
“…Pleurotus eryngii P. eryngii polysaccharides altered the abundance of SCFA producing gut bacteria [106] Pleurotus sajor-caju Growth of SCFA producing bacteria was reduced, and E.Shigella was decreased by Pleurotus sajor-caju. [113] Flammulina velutipes increase in lactic acid-producing bacteria (Lactobacillus, Lactococcus, and Streptococcus) and SCFA-producing bacteria (Allobaculum, Bifidobacterium, and Ruminococcus) [119] Hypsizygus marmoreus…”
Section: Name Of Mushroom Effect On Gut Microbiota Referencesmentioning
confidence: 99%
“…The gut microbiota, often called the “forgotten organ” or “new organ” of hosts, has a strong connection to their overall well-being [ 6 , 7 ]. Multiple research studies have suggested that a variety of human illnesses, such as obesity and related metabolic disorders, are linked to imbalances in gut microbiota [ 8 , 9 ]. The diet plays a significant role in determining the makeup of gut bacteria [ 10 ].…”
Section: Introductionmentioning
confidence: 99%